2005
DOI: 10.4049/jimmunol.175.3.1540
|View full text |Cite
|
Sign up to set email alerts
|

α-Galactosylceramide-Induced Liver Injury in Mice Is Mediated by TNF-α but Independent of Kupffer Cells

Abstract: NKT cells expressing phenotypic markers of both T and NK cells seem to be pivotal in murine models of immune-mediated liver injury, e.g., in Con A-induced hepatitis. Also α-galactosylceramide (α-GalCer), a specific ligand for invariant Vα14 NKT cells, induces hepatic injury. To improve the comprehension of NKT-cell mediated liver injury, we investigated concomitants and prerequisites of α-GalCer-induced hepatitis in mice. Liver injury induced by α-GalCer injection into C57BL/6 mice was accompanied by intrahepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
223
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(244 citation statements)
references
References 69 publications
18
223
1
2
Order By: Relevance
“…FCM data showed that 2 μg of α‐Galcer largely decreased both the per cent and number of hepatic iNKT cells within 24 hours (Figure 2A,B) which were consistent with previous report 12. Comparing with non‐α‐Galcer group, α‐Galcer strikingly increased the expression of IFN‐γ, TNF‐α, IL‐4 and CD107a in iNKT cells (Figure 2C,D).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…FCM data showed that 2 μg of α‐Galcer largely decreased both the per cent and number of hepatic iNKT cells within 24 hours (Figure 2A,B) which were consistent with previous report 12. Comparing with non‐α‐Galcer group, α‐Galcer strikingly increased the expression of IFN‐γ, TNF‐α, IL‐4 and CD107a in iNKT cells (Figure 2C,D).…”
Section: Resultssupporting
confidence: 90%
“…Specially, iNKT cells are CD1d‐restricted and can be activated by α‐Galcer, a glycolipid from marine sponge 7, 8. iNKT cells, on activation, can produce both Th1 cytokines such as IFN‐γ and Th2 cytokines such as IL‐4/IL‐13 within a few hours, the intensity and magnitude of which are closely related to various disease outcome such as cancer and infection 9, 10, 11, 12. Increasing evidence suggests that iNKT cells play a key role in anti‐HBV immunity 13, 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…5G). TNF-α released by hepatic iNKT cells plays an important role in liver damage following α-GalCer administration (26,27). Hepatic iNKT cells isolated from Raptor eKO mice produced lower levels of TNF-α than WT controls (Fig.…”
Section: Significancementioning
confidence: 97%
“…We further investigated the pathophysiological relevance of impaired iNKT-cell function in Raptor-deficient mice using a model of α-GalCer-induced hepatitis (26,27). Seventeen hours after α-GalCer injection, serum levels of alanine transaminase (ALT) and aspartate transaminase (AST), markers of liver damage, were considerably elevated in WT mice.…”
Section: Significancementioning
confidence: 99%
“…In the context of sterile inflammation, iNKT cells can have deleterious effects on local and systemic responses. For example, iNKT cells strongly participate in hepatitis induced by concanavalin A 54,68 and ␣-GalCer, 69,70 in hepatic reperfusion injury, 71,72 and in lipopolysaccharide-induced 73 or cecal ligation and puncture-mediated 74 acute septic shock. We evaluated their potential regulatory function in DENV-induced disease.…”
Section: Discussionmentioning
confidence: 99%